The Effect of Online Promotion on Consumer Buying Interest Aglonema Zaky Flowers - Dodi Aprianto; Mira Yanuarti; Cikit Apriyanti; Darwan Effendi; Gracia Gabrienda (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2023)
The computerized promotion is a device used in the current presentation of the computerized period. the number of dynamic online entertainment customers in Indonesia will reach 191 million in January 2022. Elaborate plants are currently making the beauty of many people from different walks of life. Besides having delicious varieties and shapes, elaborate plants can also be an exceptionally encouraging activity. Aglonema plant is one of the high potential ornamental plant enterprises. This study aims to find out how consumer interest in buying aglonema Zaky Flowers is affected by promotional materials and electronic word-of-mouth. Accidental sampling was used to identify respondents. In this study, multiple linear regression analysis was used to analyze the data. The sequelae of reviewing the information obtained the condition Y = - 3.109 + 0.238 X1 + 0.333 X2. The conclusion that online promotional media has a significant impact on consumers' buying interest is supported by the fact that the t-hitung value of the promotional media variable (X1) of 6,968 is greater than the value t-table of 3.177. The t-hitung esteem on the Electronic Informal (X2) variable of 13,562 is more remarkable than the t-table value of 3,177 and it is assumed that the Electronic Verbal (X2) primarily affects the expectation to buy d 'aglonema on Zaky Blossoms. The fact that the calculated F value of 234,229 is greater than the F table value of 3.09 is known.